1994
DOI: 10.1007/s001250050083
|View full text |Cite
|
Sign up to set email alerts
|

The role of reduced glucose transporter content and glucose metabolism in the immature secretory responses of fetal rat pancreatic islets

Abstract: Isolated fetal islets show an immature or poor secretory response to nutrient secretagogues which may result from impaired mitochondrial oxidative processes. Insulin secretion, glucose metabolism and detection of metabolic enzymes by radiolabelling and immunoprecipitation were compared in islets isolated from neonatal (aged 5 days) and fetal rats (at 20 days gestation). The insulin secretory dynamics of fetal islets were abnormal in response to stimulation by glucose (10 mmol/l); a rapid release of insulin rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 37 publications
2
25
0
Order By: Relevance
“…tion, even though the V max of glucokinase increased and hence glucose utilization was also significantly increased (5). Our results are in agreement with those from Rorsman et al (8) but disputed by those of Hughes (4). However, as shown by Eto et al (13), the supply of NADH to the mitochondria is more crucial to ATP synthesis and glucosestimulated insulin secretion than total glucose utilization and oxidation.…”
Section: Fig 2 Mgpdh and Mmdh Gene Expression In Adult And Fetal Issupporting
confidence: 93%
See 2 more Smart Citations
“…tion, even though the V max of glucokinase increased and hence glucose utilization was also significantly increased (5). Our results are in agreement with those from Rorsman et al (8) but disputed by those of Hughes (4). However, as shown by Eto et al (13), the supply of NADH to the mitochondria is more crucial to ATP synthesis and glucosestimulated insulin secretion than total glucose utilization and oxidation.…”
Section: Fig 2 Mgpdh and Mmdh Gene Expression In Adult And Fetal Issupporting
confidence: 93%
“…lucose is the major physiological stimulus for insulin secretion in adult ␤-cells (1-3) but is unable to cause a similar response in fetal ␤-cells (4,5). The secretion of insulin from an adult ␤-cell involves the transport of glucose into the ␤-cell via the GLUT2 transporter, followed by the production of ATP, as a result of glucose metabolism in the glycolytic pathway, the tricarboxylic acid (TCA) cycle, and the mitochondrial electron transport chain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, when we compared the expression profile of P8 mutant islets with that of controls, we found that the transcriptional programs were very similar, excluding the possibility of a pervasive developmental delay. In addition, fetal islets have a 50% reduction in protein and mRNA levels of Glut2 (42), which conceivably contributes to the lack of glucose sensitivity in fetal islets. However, both our previous studies (7) and real-time PCR from our study here revealed no difference in Glut2 mRNA expression between Foxa2 loxP/loxP ;Ins.Cre and control mice at P8.…”
Section: Discussionmentioning
confidence: 99%
“…Poor secretory responses appear not to be a consequence of inadequate insulin content of ␤-cells. Low levels of expression or activity of glucose transporters and metabolic enzymes may contribute (31,32), but other components of the secretory machinery may also be deficient in fetal and early neonatal life. The present study demonstrates that development of regulated insulin secretion after birth is accompanied by an increase in islet levels of IA-2, a tyrosine phosphatase-like protein that is proposed to mediate interactions of secretory granules with the islet cytoskeleton (12).…”
Section: Discussionmentioning
confidence: 99%